1154 The utility of the Addenbrooke's Cognitive Examination-Revised (ACE-R) in Parkinson's disease. Issue 3 (9th February 2012) - McColgan, P; Evans, J; Breen, D P; Mason, S L; Ghosh, B; Rittman, T; Rowe, J; Nestor, P; Barker, R A; Williams-Gray, C H
Abstract : Introduction: Cognitive impairment is common in Parkinson's disease (PD), even in the early stages, and appropriate screening tools which are suitable for use in the general neurology clinic are needed. Methods: We investigated the utility of the Addenbrooke's Cognitive Examination-Revised (ACE-R) as a tool for detecting mild cognitive impairment in PD (PD-MCI), defined using a detailed neuropsychological battery in an incident PD cohort. ACE-R was also validated against the Parkinson's Disease Cognitive Rating Scale (PD-CRS). We investigated the relationship between ACE-R score and behaviour and day-to-day function using the Cambridge Behavioural Inventory—Revised (CBI-R) and Parkinson's Disease Questionnaire-39 (PDQ-39). The ACE-R cognitive profile in non-demented PD was compared with profiles in of early cognitive impairment in Huntington's disease (HD), Progressive Supranuclear Palsy (PSP), amnestic mild cognitive impairment (MCI) and Alzheimer's Disease (AD). Results: 27% of the incident PD cohort were defined as PD-MCI. ROC analysis revealed an AUC for the ACE-R of 0.89 (95% CI 0.81 to 0.96). An ACE-R cut-off of <89 gave specificity 91%, sensitivity 65%, whereas a cut-off of <94 gave a sensitivity of 92% and specificity 64%. ACE-R correlated well with PD-CRS (r=0.801, p<0.0001). Significant correlations were seen between the ACE-R and CBI-R (cc=−0.249, p=<0.0001), and PDQ-39 (cc=−0.246, p=<0.0001) following adjustment for age, disease duration, Unified Parkinson's Disease Rating Scale (UPDRS) motor score and Beck Depression Inventory score (BDI). Across disease groups there was a significant difference between ACE-R profiles. Conclusion: The ACE-R is a valid screening tool for mild cognitive impairment in PD and correlates with behavioural deficits and quality of life. Furthermore it is capable of distinguishing between the cognitive profile in non-demented PD and a range of other neurological conditions.